Analysis of the Role of Product Quality and Brand Image on the Purchase Decision of Customers of Shoes Products in Jakarta - Hendy Tannady; Primadi Candra Susanto; M. Arif Hernawan; Lilik Suryaningsih; Josua Panatap Soehaditama (Jurnal Multidisiplin Madani, 2023)
The purpose of this study was to determine and analyze the effect of brand image on the decision to purchase Vans brand shoes. The second is to find out and analyze the influence of product quality on purchasing decisions for Vans brand shoes. The quantitative method is the preferred approach in this research. Researchers collected data through questionnaires. The population in this research are people who have bought Vans shoes in Jakarta. Determination of the sample used is a non-probability sampling technique with purposive sampling method. The sample used was 150 respondents with the criteria of respondents who owned and experienced the quality of Vans shoes. The conclusion of the study is that brand image variables have a significant effect on shoe purchasing decisions. The product quality variable has a significant effect on the decision to buy shoes